Chemotaxis as a navigation strategy to boost range expansion - Cremer, Jonas; Honda, Tomoya; Tang, Ying; Wong-Ng, Jerome; Vergassola, Massimo; Hwa, Terence (Nature (London), 2019)
Bacterial chemotaxis, the directed movement of cells along gradients of chemoattractants, is among the best-characterized subjects in molecular biology 1 – 10 , but much less is known about its physiological roles 11 . It is commonly seen as a starvation response when nutrients run out, or as an escape response from harmful situations 12 – 16 . Here we identify an alternative role of chemotaxis by systematically examining the spatiotemporal dynamics of Escherichia coli in soft agar 12 , 17 , 18 . Chemotaxis in nutrient-replete conditions promotes the expansion of bacterial populations into unoccupied territories well before nutrients run out in the current environment. Low levels of chemoattractants act as aroma-like cues in this process, establishing the direction and enhancing the speed of population movement along the self-generated attractant gradients. This process of navigated range expansion spreads faster and yields larger population gains than unguided expansion following the canonical Fisher–Kolmogorov dynamics 19 , 20 and is therefore a general strategy to promote population growth in spatially extended, nutrient-replete environments. Pioneering bacterial cells use chemotaxis along self-generated attractant gradients to facilitate rapid colonization of nutrient-replete environments.